Incidence of software quality attributes in the design, construction and deployment of Cloud architectural environments - Carrillo, J. (2015)
Cloud Computing (CC) is a new paradigm in world of computing, it includes several service and deployment models. This project is part of a general study that starts from the software engineering process and the software development life cycle (SDLC), this study is based on the ISO / IEC / IEEE 12207 standard, to evaluate the software implementation process and then we review some software quality aspects by applying the standard ISO / IEC 9126 which is developed for to the software product quality; finally we review some key terms, features, models, architecture, taxonomy, deployment scenarios and scope statements of Cloud Computing. After that we proceed to identify the key characteristics of private and public SaaS environments and obtained a quality model of service (QoS) using quality attributes and their corresponding metrics derived from the ISO / IEC 9126 Standard.